Expatriate return on investment (eROI) on tourism industry : a case study in Kota Kinabalu, Sabah - Norsabrina Japar (2020)
This study examines expatriate return on investment ( eROI) in the tourism industry: a case study in Kata Kinabalu, Sabah. Mc Nulty and Tharenou's (2004) propositions based on the HR stages are being adopted into this study to investigate the perceptions, experience, or perceiving thoughts among the expatriate and to see the differentiation of findings with the primary propositions proposed by the main scholar. The qualitative methods of this study received primary data from informants through the interview process and secondary data from company sources such as websites, annual reports, etc. The demographic backgrounds of the informant were from among the managers that involved in Human Resource expatriation management and the expatriate itself. This study specifically focused on the tourism industry and the data were from three categories which are expatriates, HR managers, and Immigration officers in Kota Kinabalu. The findings of this study show that expatriate ROI in the tourism industry in Kata Kinabalu related with HR stages started from the pre-departure process and administration, the on-going process of an international assignment, and the final stage of the whole process. At the same time, the tangible and intangible value showed through all the HR stages and hence, this study evaluates and makes comparative on the real experience of expatriate ROI with the theoretical models by Mc Nulty and Tharenou (2009). The study concluded how the expatriate ROI gives a positive impact on the economy in Kota Kinabalu, Sabah. Hence, it is very significant to highlight the role of these expatriates and the HR managers involving in the tourism sector as a human capital investment that capable to stimulate the economic influence in Kota Kinabalu, Sabah.